Stonehenge
The early work at Stonehenge consisted of an earthwork circle and an entrance, marked by one large stone and a pair of small ones. The bank and ditch of the original earthwork can be seen in the foreground, and the large standing stone on the extreme left marks the entrance. There was probably some building at or near the center, but this has been removed, and the present central structure dates from later periods.